Multi-objective probabilistic fractional programming problem involving two parameters Cauchy distribution - Acharya, Srikumar; Belay, Berhanu; Mishra, Rajashree (Mathematical Modelling and Analysis, 2019)
The paper presents the solution methodology of a multi-objective probabilistic fractional programming problem, where the parameters of the right hand side constraints follow Cauchy distribution. The proposed mathematical model can not be solved directly. The solution procedure is completed in three steps. In ﬁrst step, multi-objective probabilistic fractional programming problem is converted to deterministic multi-objective fractional mathematical programming problem. In the second step, it is converted to its equivalent multi-objective mathematical programming problem. Finally, ε -constraint method is applied to ﬁnd the best compromise solution. A numerical example and application are presented to demonstrate the procedure of proposed mathematical model.